Treatment of Gangrenous Phalanx using combination therapy of Platelets Rich Plasma (PRP) and Photo Bio Modulation (PBM): Treatment of Gangrenous Phalanx using Combination Therapy - Anwar, Shahzad; Akram, Sania; Abbas, Zaigham (Pakistan Journal of Health Sciences, 2023)
Gangrene is a dangerous and potentially fatal condition that happens when the blood flow to an area of tissue or organ is cut off. This causes the tissue to break down and die. Gangrene often turns the affected skin a greenish-black color. Due to poor attention and unhygienic conditions, this becomes more contaminated and in the end amputation remains the only treatment option. Traditional therapies cannot provide necessary growth factors to regenerate. Platelet Rich Plasma (PRP) helps in wound healing process by releasing various growth factors. Photo bio modulation (PBM) is also reported for this purpose. Objectives: To evaluate the safety and efficacy of PRP and PBM for the treatment of dry gangrene in the fractured little finger in a roadside accident. Methods: We report a case of a twenty-seven-year-old male with fractured little finger (Phalanx) in a roadside accident. The patient reported after 6 weeks with dry gangrene and severe pain. The patient treated with combination of PRP and PBM. Results: Over a follow up of six weeks, significant improvement was shown with decrease in pain. Little finger was recovered that was showing mobility and growing nail. Conclusion: It is concluded that PRP along with PBM is an effective treatment for dry gangrene.